The Hippo–YAP pathway in organ size control and tumorigenesis: an updated version - Zhao, Bin (Cold Spring Harbor Laboratory Press, 2010)
The Hippo signaling pathway is gaining recognition as an important player in both organ size control and tumorigenesis, which are physiological and pathological processes that share common cellular signaling mechanisms. Upon activation by stimuli such as high cell density in cell culture, the Hippo pathway kinase cascade phosphorylates and inhibits the Yes-associated protein (YAP)/TAZ transcription coactivators representing the major signaling output of the pathway. Altered gene expression resulting from YAP/TAZ inhibition affects cell number by repressing cell proliferation and promoting apoptosis, thereby limiting organ size. Recent studies have provided new insights into the Hippo signaling pathway, elucidating novel phosphorylation-dependent and independent mechanisms of YAP/Yki inhibition by the Hippo pathway, new Hippo pathway components, novel YAP target transcription factors and target genes, and the three-dimensional structure of the YAP–TEAD complex, and providing further evidence for the involvement of YAP and the Hippo pathway in tumorigenesis.